Predictors of quality interactions among Filipino children and their parents - Bartolome, Teresita Chico (2004)
This study aimed to to determine the predictors of quality interaction in the different aspects of development among Filipino children and their parents. A total of 319 parent and children respondents from selected public and private elementary schools in Quezon City participated in the study. A research-made questionnaire was used. Frequency, percentage, mean, t-test, and regression analysis were the statistical tools used. Significance level was set at 0.01 and 0.05. The parental characteristic that best predicted the quality of interaction was the number of children for the emotional, intellectual, and sociological aspects. The characteristics of children that best predicted quality interaction were gender on physiological, and emotional aspect of interaction. The result of the focus group discussions revealed that there is a need for a more open communication between the parents and their children.